Autologous pericardium used for reconstruction of left innominate vein in patient with mediastinal venous aneurysm:a case report - Fang, Cheng (BMC Surg, 2020)
BACKGROUND: Mediastinal venous aneurysm is a very rare disease and can be easily misdiagnosed. Patients are often asymptomatic while venous aneurysm of large size with adjacent structures oppressed can lead to discomfort. The surgical treatment for aneurysm of large vessels is often complex and challenging. CASE PRESENTATION: We reported a 52-year-old man with mediastinal mass who received operation on July 2019 in our hospital. Left innominate vein aneurysm was diagnosed during operation with superior vena cava involved. The aneurysm was resected and pericardium was taken to repair part wall of superior vena cava and reconstruct left innominate vein. The patient’s postoperative course was uneventful. CONCLUSIONS: Venous aneurysm should be considered when mediastinal mass has no clear boundary with large veins or even seems to connect with them. Magnetic resonance imaging, computed tomographic angiography and invasive venography can be performed to further evaluate the mass once diagnosis of venous aneurysm was suspected. Using pericardium to repair large veins is a good choice which is safe and costless.